Bioleaching for critical metal recovery from bauxite residue- unlocking waste valorization - Soto-Montandon, Fernanda; Gillane, Rosemary; Marcellin, Esteban; Harrison, Susan T. L.; Villa-Gomez, Denys (Frontiers in Bioengineering and Biotechnology, 2025)
The increasing problem of waste from alumina refineries endangers ecosystems and local communities. With over 4 billion tons of bauxite residue stored globally, more than 140 million tons generated annually, and less than 3% currently reused, the situation is unsustainable. However, bauxite residue also contains critical metals essential for advancing sustainable technologies, aligning with the United Nations’ 7th Sustainable Development Goal (SDG). Fully recovering these valuable elements and reusing the waste not only addresses environmental concerns but also supports a resilient and sustainable supply of materials needed for the green energy transition. Given the environmental drawbacks of traditional extraction methods, biotechnological approaches show promise as an environmentally responsible and cost-effective alternative, reinforcing circular economy principles and supporting the 12th SDG, which promotes responsible resource use and the reduction of hazardous waste. This review offers a novel, integrated evaluation of bauxite residue valorization, combining an overview of its composition and characteristics with a detailed examination of bioleaching-based recovery of rare earth elements, gallium, vanadium, and titanium. Special emphasis is placed on selecting optimal microorganisms, understanding the metabolic pathways behind bioleaching agent production, and refining strategies to enhance process efficiency and microbial performance. Additionally, it highlights how circular economy approaches can drive resource-efficient and sustainable utilization of alkaline residues, providing a perspective not covered in previous studies.